2014
DOI: 10.1155/2014/604737
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Endoscopy with Narrow Band Imaging to Determine the Extent of Resection in Transoral Robotic Surgery of Oropharyngeal Cancer

Abstract: Transoral robotic surgery (TORS) is a less invasive treatment that is becoming popular all over the world. One of the most important factors for achieving success in TORS is the ability to determine the extent of resection during the procedure as the extent of resection in the laryngopharynx not only affects oncological outcomes but also directly affects swallowing and voice functions. Magnifying endoscopy with narrow band imaging (ME-NBI) is an innovative optical technology that provides high-resolution image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…OPSCC has been addressed in 2 different case series. Patsias et al 36 showed that the use of high-resolution microendoscopy imaging during transoral robotic surgery (TORS) might provide real-time histological assessment of tumor margins, while Tateya et al 37 evaluated the feasibility and efficacy of NBI in determining the extent of OPSCC resection by TORS and found that it enabled an estimation of the horizontal extent of the superficial lesion and detection of surrounding superficial lesions normally not identified without NBI.…”
Section: Discussionmentioning
confidence: 99%
“…OPSCC has been addressed in 2 different case series. Patsias et al 36 showed that the use of high-resolution microendoscopy imaging during transoral robotic surgery (TORS) might provide real-time histological assessment of tumor margins, while Tateya et al 37 evaluated the feasibility and efficacy of NBI in determining the extent of OPSCC resection by TORS and found that it enabled an estimation of the horizontal extent of the superficial lesion and detection of surrounding superficial lesions normally not identified without NBI.…”
Section: Discussionmentioning
confidence: 99%
“…Ein weiterer möglicher Ansatz ist die Anwendung von Endoskopen mit bis zu 80facher Vergrößerungsmöglichkeit (‚magnification endoscopy') in Kombination mit NBI. Diese wurden beispielsweise für die Bestimmung der chirurgischen Absetzungsgrenzen bei der transoralen robotischen Chirurgie (TORS) angewendet [23].…”
Section: Die Eindringtiefe Für Blaues Licht Bei 40 Nm Beträgt Nachunclassified
“… Pharynx [23–30] : This category includes the publications for TORS in pharynx [23–25], nasopharynx (NP) [26] – located to the upper part of the pharynx –, parapharynx space tumours [27, 28] – located deep within the neck and it is a potential space lateral to the upper pharynx – and retropharynx [29, 30] – which is the posterior part of the pharynx – (see Table 2). Oropharynx [1, 31–52] : This category includes all the publications related to TORS, which refer to oropharyngeal carcinomas and tumours. The first subcategory includes publications which present the outcomes following TORS for oropharynx squamous cell carcinoma (OPSCC), such as swallowing, speech and quality of life (QOL) [40], the oncologic and functional outcomes [39, 52], postoperative bleeding with and without external carotid artery ligation [44].…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…Also, there are publications which compare the oncologic and functions between TORS and a treatment‐surgical approach [46], such as TORS versus definitive chemo‐radiotherapy (CRT) [41] and TORS versus traditional open surgical approaches [43]. The second subcategory includes publications which present a modified TORS approach, such as using magnifying endoscopy with narrow band imaging (ME‐NBI) with TORS in order to provide high‐resolution images and to detect early superficial pharyngeal cancers [34], or using a miniaturised high‐resolution fiberoptic microendoscope with TORS for providing real‐time histological assessment [36]. Also, another publication proposes a modified TORS approach in which transoral mandibular osteotomies are performed that can greatly improve exposure to oropharyngeal subsites and expand access to the larynx in selected patients [37].…”
Section: State‐of‐the‐artmentioning
confidence: 99%